Effectiveness and Implementation Barriers of Preoperative Education on Surgical Patient Outcomes: A Scoping Review - Putri, Kartika Nurif Adeline; Rondhianto, Rondhianto; Rifai, Ahmad (Journal of Applied Nursing and Health, 2026)
Background: Preoperative education improves patients’ understanding and reduces anxiety before surgery. However, evidence regarding its effectiveness and contextual factors remains inconsistent and fragmented. Therefore, this scoping review aims to map the effectiveness and limitations of preoperative education on surgical patient outcomes. Methods: This study used a scoping review design based on PRISMA-ScR, the PCC (Population, Concept, Context) framework, and the Arksey & O’Malley method. A systematic search was conducted in four databases (Scopus, SpringerLink, PubMed, ScienceDirect) for articles published between 2022 and 2026. The study selection process included duplicate removal, title and abstract screening, and full-text review based on predefined eligibility criteria. Data were extracted using a standardised charting form by independent reviewers, with discrepancies resolved through discussion. The extracted data were analysed using thematic synthesis to identify key themes related to effectiveness and implementation barriers. Results: A total of 514 records were identified from four databases. After excluding articles that were not full-text, not open access, or not written in English (n=207), 307 articles remained for screening. During the screening stage, 263 records were excluded due to duplicate removal, irrelevant titles and abstracts, inappropriate population, intervention, or study type. A total of 44 full-text articles were assessed for eligibility, of which 24 were excluded for not explicitly addressing preoperative education as the primary focus. No studies were excluded based on quality assessment. Finally, 20 studies were included in the review. Three main themes emerged from the synthesis: (1) Cognitive and psychological effectiveness, where most studies reported improvements in patient knowledge and reduced anxiety, although some studies found limited or non-significant effects; (2) Clinical and health system outcomes, including pain reduction, reduced opioid use, postoperative recovery metrics, patient satisfaction, and healthcare service efficiency, although findings varied across contexts and populations; and (3) Implementation barriers and limitations, including variability in educational delivery, timing, digital technology effectiveness, patient characteristics, and methodological constraints. Overall, substantial heterogeneity in effectiveness was observed, along with gaps in integrating multidimensional outcomes and standardizing educational approaches. Conclusion: Preoperative education is a beneficial intervention that can improve clinical outcomes and healthcare efficiency, although its effects vary across populations and settings. These findings support the need for standardized, context-adaptive educational protocols and further high-quality studies to evaluate their effectiveness